Estudo da computação de descritores de reatividade de um sistema polipeptídico usando hamiltonianos semi-empírico - Grillo, Igor Barden (2019)
Reactivity descriptors are theoretical quantities retrieved from the molecular electronic structure, convenient to preliminary reactions study and/or their rationalization. A class of these reactivity descriptors, based on the electronic density response variables, have being largely employed to the theoretical study of chemical reactions involving organic molecules. Due to the lower computational cost, compared to the a entire reaction simulation, these descriptors become an attractive alternative to preliminary reactivity studies of macromolecules relevant to drug development. Still,the computational cost using ab-initio/DFT methods to calculate macromolecules make the calculations impractical. Approximated methods, such semiempirical Hamiltonians, may be the way to turn these reactivity descriptors calculations possible. These methods are not well explored to get such quantities, and therefore in this study we propose the comparison of reactivity descriptors from Conceptual Density Functional Theory between an often used DFT calculation protocol and semiempirical Hamiltonians for a protein-like structure. A systematic comparison was conducted exploring well established global and local reactivity descriptors with different approximations and representation types found in literature which are successfully applied for small molecules. We showed that it is possible to use semiempirical Hamiltonians as electronic structure method to calculate reactivity descriptors for macromolecules. The best performance was achieved using frontier orbital energies and densities combined with the Localized Molecular Orbital scheme MOZYME.